FE Simulation of Transmission Tower - Boshra Eltaly; Amen Saka; Kamel Kandil (Advances in Civil Engineering)
The vital components of the transmission line are the electrical transmission towers. They are commonly used to support the phase conductors and shield wires of a transmission line. Also the accurate prediction of tower failure is very important for the reliability and safety of the transmission system. The current research describes nonlinear FE models of predicting the transmission tower failure. In the current FE simulations, the eccentricity and the joint effect of the tower were considered. The current models have been calibrated with results from previous full-scale tower tests and numerical models with good accuracy in terms of both the failure load and the failure mode.